Physiological and Root Profile Studies of Four Legume Tree Species - Saifuddin, M.; Osman, Normaniza (Marsland Press, 2012)
It is a great challenge for researchers to select plant species in terms of their physiological and root properties for vegetation on slope. Therefore, this study was aimed to investigate the physiology and root profile of four selected tropical plants namely Leucaena leucocephala (LL), Adenanthera pavonina (AP), Peltophorum pterocarpum (PP) and Pterocarpus indicus (PI). The species studied were grown in three different types of soil; slope, clay and sandy, under greenhouse conditions. Outstanding physiological performance, as measured by chlorophyll fluorescence, the photosynthetic rate, the biomass production and growth rate were observed to be the highest in LL, followed by PP, AP and PI. In terms of the root profiles, LL exhibited a higher root length (450%), volume (500%), and root biomass (600%) than PI. The root biomass values of the species studied was highly correlated with the soil moisture content (R2=0.83). Overall results suggested that L. leucocephala exhibited outstanding physiological performance and root profiles and can be a potential plant for soil reinforcement. [Saifuddin M, Normaniza O. Physiological and root profile studies of four legume tree species.